Improving quality of care in Saudi Arabia: An Interprofessional Practice Model and Evidence based practice approach - Moussa, Fatchima L (IJRDO-Journal of Applied Science, 2019)
From the nursing perspective, interprofessional collaboration is important as it helps to ensure that a greater continuity and quality of care can be provided to patients, which is the nurse’s top aim. Interprofessional collaboration allows patient centered care to be more fully realized by nurses. Evidence-based practice also facilitates the delivery of quality care by nurses. The more that nurses are able to work with other health care professionals, communicate effectively with them, share information, and collaborate with them, the more the patient is likely to benefit. This chapter discusses the ways in which nurses in Saudi Arabia can think about interprofessional collaboration and evidence-based practice as conduits to patient centered, quality care.